Pelaksanaan Peraturan Daerah Kabupaten Karanganyar Nomor 10 Tahun 2015 Terkait dengan Pengelolaan Badan Usaha Milik Desa di Desa Berjo Kecamatan Ngargoyoso Kabupaten Karanganyar - Nurjati, Aditya Luthfi; Madalina, Maria (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2021)
ABSTRACTThe legal issue in this paper is the implementation of Karanganyar Regency Regulation Number 10 of 2015 concerning Village-Owned Enterprises related to the implementation of Village-Owned Enterprises named Sumber Mulyo in Berjo Village, Ngargoyoso District, Karanganyar Regency. This study also aims to determine the inhibiting factors and constraints that occur in the management of Sumber Mulyo Village Owned Enterprises in the framework of implementing the Karanganyar District Regulation Number 10 of 2015. The results of this study stated that the implementation of Regional Regulation Number 10 of 2015 Associated with Village-Owned Enterprises in Berjo Village, Ngargoyoso District whose implementation was in accordance with the mechanism of Regional Regulation of Karanganyar Regency Number 10 of 2015 and also in line with existing objectives. Obstacles in the implementation of the regional regulation are in line with the Human Resources (HR) both from the lack of awareness of the citizens and the lack of experts.Keywords : implementation; regional regulation; village; village-owned enterprises.